2004
DOI: 10.1016/j.joca.2004.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical stimulation with electromagnetic field and insulin growth factor-I treatment on proteoglycan synthesis of bovine articular cartilage

Abstract: The results of this study show that EMF can act in concert with IGF-I in stimulating PG synthesis in bovine articular cartilage explants. As this effect is not maintained in chondrocyte monolayers, the native cell-matrix interactions in the tissue may be fundamental in driving the EMF effects. These data suggest that in vivo the combination of both EMF and IGF may exert a more chondroprotective effect than either treatment alone on articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 50 publications
5
92
1
1
Order By: Relevance
“…Proteoglycan synthesis was determined by radioactive sulfate incorporation into glycosaminoglycans (GAGs), which are biochemical components of PGs, during 1 or 7 days of culture, as previously reported [De Mattei et al, 2004]. Briefly, 5 mCi/ml of Na 2 -35 SO 4 (2.2 mCi/ml; Amersham Pharmacia Biotech, Buckinghamshire, England) was added to the culture media of both unexposed and exposed explants at time 0 and when the medium was replaced (3rd day).…”
Section: Quantification Of Pg Synthesis and Releasementioning
confidence: 99%
“…Proteoglycan synthesis was determined by radioactive sulfate incorporation into glycosaminoglycans (GAGs), which are biochemical components of PGs, during 1 or 7 days of culture, as previously reported [De Mattei et al, 2004]. Briefly, 5 mCi/ml of Na 2 -35 SO 4 (2.2 mCi/ml; Amersham Pharmacia Biotech, Buckinghamshire, England) was added to the culture media of both unexposed and exposed explants at time 0 and when the medium was replaced (3rd day).…”
Section: Quantification Of Pg Synthesis and Releasementioning
confidence: 99%
“…Although numerous studies have examined the effects of electromagnetic field on differentiation and gene expression of chondrocytes, few studies have assessed MSCs. 33,34 With the cartilage explants, an electromagnetic field (75 Hz, 1.5 mT) significantly increased not only the 35 S-sulfate incorporation and the cartilage-specific proteins levels but also messenger RNA of aggrecan and type II collagen. Compared to our electromagnetic field system, these studies used much higher frequencies and intensities.…”
Section: Discussionmentioning
confidence: 97%
“…The modulation of these receptors is possibly one of the mechanisms by which the PEMF counteracts the effect of pro-inflammatory cytokines in explants of cartilage and synovial fibroblasts and prevents the progression to OA [7,11,12]. On the other hand, bovine and human models have shown that PEMFs through a synergy with insulin-like Growth Factor 1 (IGF-1) exerts a pro-anabolic activity enhancing chondrogenic differentiation and synthesis of extra-cellular matrix component [9,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated an influence on cartilage metabolism through pro-anabolic and anti-catabolic activity, which has generated interest in the use of PEMFs [7][8][9][10][11][12]. PEMFs were introduced in the clinical setting in the 1970s as a successful method for treatment of non-union and delayed union of fractures; the effects on focal cartilage lesions of the knee remain unknown while studies on OA are equivocal [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%